Protein Adsorption and Conformational Changes - Michael Assfalg (Molecules, 2021)
Protein adsorption onto surfaces of diverse materials of both natural and artificial origin is of utmost relevance in many areas of research and technology: medicine, pharmaceutical sciences, analytical sciences, biotechnology, nanotechnology, and cell biology, among others [...]